Interpreting functional imaging studies in terms of neurotransmitter cycling - Shulman, Robert G. (National Academy of Sciences, 1998)
Functional imaging experiments, in particular positron-emission tomography and functional magnetic resonance imaging, can be analyzed either in psychological terms or on the basis of neuroscience. In the usual psychological interpretation, stimulations are designed to activate specific mental processes identified by cognitive psychology, which are then localized by the signals in functional imaging experiments. An alternate approach would be to analyze experiments in terms of the neurobiological processes responsible for the signals. Recent in vivo (13)C NMR measurements of the glutamate-to-glutamine neurotransmitter cycling in rat and human brains facilitate a neuroscientific interpretation of functional imaging data in terms of neurobiological processes since incremental neurotransmitter flux showed a 1:1 stoichiometry with the incremental rate of glucose oxidation. Because functional imaging signals depend on brain energy consumption, a quantitative relationship can be established between the signal (S) and the specific neurochemical cerebral neurotransmitter activity (N) of glutamate-to-glutamine neurotransmitter cycling. The quantitation of neuronal activity proposed has implications for the psychological design and interpretation of functional imaging experiments. Measurements of the neurotransmitter cycling flux at rest in functional imaging experiments suggest that performing cognitive tasks and sensory stimulations increases neurotransmitter cycling by only 10–20%. Therefore it cannot be assumed that reference state activities are negligible, nor that they are constant during stimulation.